A SPEECH ACT ANALYSIS OF SANUSI LAMIDO SANUSI’S SPEECH AT THE 60TH BIRTHDAY CELEBRATION OF NASIR-EL-RUFAI, GOVERNOR OF KADUNA STATE, NIGERIA - ONONIWU, Mark Chitulu; ONUIGBO, Sam M. (EBSU Journal of Social Sciences and Humanities, 2021)
This research discusses the types of illocutionary acts used in Sanusi Lamido Sanusi’s speech at the 60th birthday celebration of Nasir-El-Rufai, governor of Kaduna State, Nigeria on the 23rd of February, 2020. The reader is made to see the inner thoughts of Sanusi Lamido Sanusi through his illocutionary force. The research used the speech act theory of John Searle (1999) to make a very deep foray into the mind of Sanusi Lamido Sanusi who will henceforth be referred to as SLS. Through this means, the inner thoughts of his mind are brought to the fore. In addition, the illocutionary force that accompanies his utterances is laid bare for all to see, throwing more light on how he has been able to sway his audience to his side. The method employed in this study is a textual analysis of data from the speech of SLS using John Searle’s Speech Act Theory as the tool for analysis. This resulted in the exposure and revelation of the inner thoughts of SLS concerning the unsavory, socio-political and economic state of affairs in the North of Nigeria. The research totally unveiled the illocutionary forces of the speech acts of Sanusi Lamido Sanusi which naturally elicited very terse reactions from the audience in the pragmatic contexts of the speech.